Structure and properties of the Adriatic crust in the central‐eastern Southern Alps (Italy) from local earthquake tomography. (27th August 2013) - Viganò, Alfio; Scafidi, Davide; Martin, Silvana; Spallarossa, Daniele
Abstract: Structure and properties of the Adriatic crust were determined from local earthquake tomography around the Giudicarie fault zone (central‐eastern Southern Alps, Italy). Tomographic results, based on well‐suited 436 revised earthquakes (period 1994–2007), have a resolution comparable to the scale of regional geological domains and tectonic structures. The observed strong velocity anomalies correlate well with lithological variations corresponding to different geological domains (particularly magmatic complexes at depth) and with high fracturing and/or presence of fluids along active fault systems (South Giudicarie and Valsugana–Bassano del Grappa–Montello thrusts).